TEORI KONTINJENSI, SISTEM PENGENDALIAN MANAJEMEN DAN OUTCOMES PERUSAHAAN: IMPLIKASINYA DALAM RISET MASA KINI DAN MASA YANG AKAN DATANG - Atik Sri Purwati; Siti Zulaikha (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2005)
This paper examines the link between contingency theory and management control systems. Contingency theory states that the design and use of control systems is dependent upon the context of the organizational setting. A better match between the control systems to the contingency variable’s hypothesized to result in increased organizational performance, This paper identifies contingent control variables, defines the boundaries of control systems, and categorizes prior work by the analysis complexity. Even though this research stream has provided useful insights, may of the results are tentative and less than definitive. This paper concludes by proposing ways to stregthen contingency theory results.